ANALISIS KESIAPAN DAN KEBERLANJUTAN PROGRAM MERDEKA BELAJAR KAMPUS MERDEKA (STUDI KASUS UNIVERSITAS MUHAMMADIYAH JAMBI) - Helmina Helmina; Yahfenel Evi Fussalam; Resi Silvia; Yusrizal Yusrizal (Jurnal Muara Pendidikan, 2022)
This study aims to analyze (1) how the academic community understands the Independent Learning Campus (MKBM) policy, and (2) what are the supporting factors and inhibiting factors in the implementation of the MKBM program at the Muhammadiyah University of Jambi. The research method used is a mixed research method that combines a quantitative approach through surveys and a qualitative approach with interviews as an instrument in data research. Research informants came from the academic community who collected 550 people ranging from leaders, educators (lecturers), education staff, librarians, laboratory officers, and students of the Muhammadiyah Jambi University who were selected through purposive sampling. The survey results showed that the informants did not fully understand the MBKM program where 44% stated that they only knew, 27% were confused, 18% knew most of the MBKM program, 9% understood the MBKM program, and 2% did not fill out or choose. The results of the interviews illustrate that the preparation of the MBKM program has been running with a structured and systematic system. Although the informant also stated that the independent learning program was still new, funding or budget, quality of human resources, and supervision (process and results) were the determining factors supporting as well as inhibiting the readiness and sustainability of the MBKM program.